2019
DOI: 10.1371/journal.ppat.1007744
|View full text |Cite
|
Sign up to set email alerts
|

MyD88 and IL-1R signaling drive antibacterial immunity and osteoclast-driven bone loss during Staphylococcus aureus osteomyelitis

Abstract: Staphylococcus aureus is able to infect virtually all organ systems and is a frequently isolated etiologic agent of osteomyelitis, a common and debilitating invasive infection of bone. Treatment of osteomyelitis requires invasive surgical procedures and prolonged antibiotic therapy, yet is frequently unsuccessful due to extensive pathogen-induced bone damage that can limit antibiotic penetration and immune cell influx to the infectious focus. We previously established that S .… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
85
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 60 publications
(94 citation statements)
references
References 85 publications
(131 reference statements)
2
85
0
3
Order By: Relevance
“…The same cytokines that are needed for efficient antibacterial immune responses may also drastically affect the activity of bone cells . It can be reasoned that the inflammatory response in bacterial infection is a double‐edge sword in terms of its opposite effects on osteogenesis.…”
Section: What Is the Mechanism Of The Observed Pro‐osteogenic Responsmentioning
confidence: 99%
See 3 more Smart Citations
“…The same cytokines that are needed for efficient antibacterial immune responses may also drastically affect the activity of bone cells . It can be reasoned that the inflammatory response in bacterial infection is a double‐edge sword in terms of its opposite effects on osteogenesis.…”
Section: What Is the Mechanism Of The Observed Pro‐osteogenic Responsmentioning
confidence: 99%
“…In this context, the activation of various pattern recognition receptors (PRRs) in osteomyelitis may be an important shared feature of the different, sometimes paradoxical, cellular responses seen in osteomyelitis. In recent years, it has been shown that PRRs not only play a key role in the antibacterial immune response, but that they also modulate the osteoblastic and osteoclastic responses …”
Section: What Is the Mechanism Of The Observed Pro‐osteogenic Responsmentioning
confidence: 99%
See 2 more Smart Citations
“…Investigation into the role of OCs in OM has focused mainly on determining the effects of S. aureus infection on bone resorption, while neglecting to examine whether OCs could be the target of infection, as well. [17, 18, 19, 20].…”
Section: Introductionmentioning
confidence: 99%